2002
DOI: 10.1007/s00284-001-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Thermostable Direct Hemolysin Produced by Vibrio parahaemolyticus O3:K6 and Other Serovars Grown Anaerobically with the Presence of a Bile Acid

Abstract: Twenty-three V. parahaemolyticus strains, including 12 pandemic O3:K6 strains, were examined for their growth and production of thermostable direct hemolysin (TDH) under an anaerobic culture condition with or without presence of a bile acid, taurocholic acid (TCA). Both bacterial growth and TDH production were markedly enhanced by TCA for a majority of the strains, but the scale of the TDH production was disproportionately greater than that of the corresponding growth for 14 strains. Such enhancement was, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Osawa et al demonstrated that production of TDH by V. parahaemolyticus was enhanced by several bile acids [35], [36]. It was also reported that bile and DC increased adherence of both KP-positive and KP-negative V. parahaemolyticus to Int-407 cells in vitro [37]. Recently, it was reported that bile modulated T3SS genes expression of non-O1/non-O139 V. cholerae [38].…”
Section: Discussionmentioning
confidence: 99%
“…Osawa et al demonstrated that production of TDH by V. parahaemolyticus was enhanced by several bile acids [35], [36]. It was also reported that bile and DC increased adherence of both KP-positive and KP-negative V. parahaemolyticus to Int-407 cells in vitro [37]. Recently, it was reported that bile modulated T3SS genes expression of non-O1/non-O139 V. cholerae [38].…”
Section: Discussionmentioning
confidence: 99%
“…For many enteric pathogens, bile and deoxycholate are important host intraintestinal signaling molecules that serve to regulate the expression of virulence factors during infection. For example, bile can repress SPI1 T3SS-mediated invasion of Salmonella spp., and in V. parahaemolyticus, bile acids enhance the production of the thermostable direct hemolysin, which is an essential virulence factor (56,(59)(60)(61). Regulation can also occur at the protein level, and bile salts have been shown to act as environmental signals for the stable recruitment of IpaB onto the Shigella needle tip complex (74).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids play a key role in the pathogenicity of Vibrio species. Conjugated bile acids enhance production of V. parahemolyticus thermostable direct hemolysin (TDH), a virulence factor produced by strains most frequently associated with disease [245,246]. In addition, bile acids enhance the expression of other attributes associated with virulence such as Congo red binding ability, capsule production and adherence to epithelial cells [247].…”
Section: Bile and Pathogenesismentioning
confidence: 99%